2021
DOI: 10.1016/j.annepidem.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of race, socioeconomic status, and comorbidity on patients afflicted with COVID 19: A Local Perspective

Abstract: Purpose: The aim of this study is to further examine the associations of race, socioeconomic factors, and comorbidity with COVID-19 health outcomes. Methods: This is a retrospective cohort study of 309 PCR confirmed COVID-19 positive adults who presented to Tulane Medical Center in New Orleans, LA, from March 9 to May 29, 2020. The primary outcomes investigated were need for invasive mechanical ventilation (IMV) and in-hospital mortality. A multivariate analysis was performed to determine socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This study also investigates the association between vaccine acceptance, economic stress, and opinions about the government’s response, while controlling for sociodemographic and health determinants. As expected, our results indicate that people who are more likely to experience severe consequences from the infection, such as those ≥45 years and those with comorbidities are also more willing to get vaccinated [ 29 , 30 ]. In addition, similar to other studies, our results show that having a previous COVID-19 diagnosis and past refusal of other vaccines are associated with lower COVID-19 vaccine acceptance [ 10 , 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…This study also investigates the association between vaccine acceptance, economic stress, and opinions about the government’s response, while controlling for sociodemographic and health determinants. As expected, our results indicate that people who are more likely to experience severe consequences from the infection, such as those ≥45 years and those with comorbidities are also more willing to get vaccinated [ 29 , 30 ]. In addition, similar to other studies, our results show that having a previous COVID-19 diagnosis and past refusal of other vaccines are associated with lower COVID-19 vaccine acceptance [ 10 , 31 ].…”
Section: Discussionsupporting
confidence: 64%
“…A similar result was observed in a population-based serological survey in Switzerland. 23 Considering the differences in the risk of infection according to the socio-economic level described in previous research, 24,25 the seroprevalence patterns observed according to educational level possibly indicate a greater adherence to public health measures in subgroups-with a higher level of education. Our results may also reflect lower adherence to vaccination by those with lower health literacy which is correlated with lower levels of education.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the underweight group presented an increased risk of death, whilst no association with the need for intensive mechanical ventilation was found [35,36]. In the evolution of the disease, those with mild and moderate obesity are predisposed to develop more severe ARDS, and paradoxically they recover better [39].…”
Section: Discussionmentioning
confidence: 95%